2015
DOI: 10.1007/s10875-015-0160-6
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of OKT3 MAb to Patients with NASH, Promotes Regulatory T-cell Induction, and Alleviates Insulin Resistance: Results of a Phase IIa Blinded Placebo-Controlled Trial

Abstract: Oral administration of anti-CD3 MAb to patients with NASH was safe and well tolerated. Positive biological effects were noted in several hepatic, metabolic and immunologic parameters. These findings provide the basis for future trials to investigate the effect of oral anti-CD3 MAb immunotherapy in patients with NASH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 33 publications
1
47
0
Order By: Relevance
“…However, although TGF-β has been described as a pro-fibrogenic cytokine [41], an increase in TGF-β serum levels is associated with improvement in liver function in NASH [42]. Alternatively, the balance between other cytokines and adipokines not measured in this study may explain the noted effect.…”
Section: Discussionmentioning
confidence: 73%
“…However, although TGF-β has been described as a pro-fibrogenic cytokine [41], an increase in TGF-β serum levels is associated with improvement in liver function in NASH [42]. Alternatively, the balance between other cytokines and adipokines not measured in this study may explain the noted effect.…”
Section: Discussionmentioning
confidence: 73%
“…The drug was well tolerated without any treatment-related adverse reactions [81]. The drug was well tolerated without any treatment-related adverse reactions [81].…”
Section: Immunotherapy For Nash By Oral Administration Of Anti-cd3mentioning
confidence: 92%
“…A treatment regime of five-times 1 mg was considered superior to 0.2 or 5 mg [107]. Two single blind randomized placebo controlled Phase IIa studies in patients with treatment resistant chronic hepatitis C infection (HCV) [108] or nonalcoholic steatohepatitis (NASH) and altered glucose metabolism that included subjects with Type 2 diabetes [109], demonstrated that oral CD3 was safe and well tolerated, as measured by blood hematology, chemistry, immunological safety markers and physical signs [108,109]. Both studies reported positive effects on disease and immunological markers including an increase of Tregs [108,109].…”
Section: Clinical Trials With Oral Anti-cd3 Mabmentioning
confidence: 99%
“…A very promising approach to improve safety is oral or nasal administration of anti-CD3 mAb. Clinical data showed promising results in terms of safety and therapeutic effect [107,109]. Future development in anti-CD3 immunotherapy warrants further clinical studies to explore the potential of mucosal anti-CD3 mAb therapy for treatment of a wide range of autoimmune and inflammatory diseases in humans.…”
Section: Combination Therapies With Anti-cd3 Mab To Improve Safetymentioning
confidence: 99%
See 1 more Smart Citation